2018
DOI: 10.1182/bloodadvances.2018017293
|View full text |Cite
|
Sign up to set email alerts
|

Blood group ABO gene–encoded A transferase catalyzes the biosynthesis of FORS1 antigen of FORS system upon Met69Thr/Ser substitution

Abstract: Blood group A/B glycosyltransferases (AT/BTs) and Forssman glycolipid synthase (FS) are encoded by the evolutionarily related (A/B alleles) and genes, respectively. AT/BT and FS catalyze the biosynthesis of A/B and Forssman (FORS1) oligosaccharide antigens that are responsible for the distinct blood group systems of ABO and FORS. Using genetic engineering, DNA transfection, and immunocytochemistry and immunocytometry, we have previously shown that the eukaryotic expression construct encoding human AT, whose Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Similar to the results of DNA transfection with the human AT constructs without the LeuGlyGly266-268GlyGlyAla substitution described above, the positive and negative controls presented anticipated positive and negative results. In addition, the amino acid substitution constructs at codon 69 exhibited substantially higher FORS1 antigen expression when combined with the LeuGlyGly266-268GlyGlyAla substitution, possibly due to the synergistic effects previously reported of the AT constructs containing the deletion of exon 3 or 4, or Met69Ser/Thr substitution in combination with the LeuGlyGly266-268GlyGlyAla substitution 16,24 . However, the Ter construct, H_ABO-A(Met69Ter & GlyGlyAla), did not present any FS activity even with the LeuGlyGly266-268GlyGlyAla substitution.
Figure 6FORS1 antigen expression after DNA transfection of a variety of human AT amino acid substitution constructs at codon 69 with the LeuGlyGly266-268GlyGlyAla substitution into COS1(B3GALNT1 + A4GALT) cells analyzed by immunocytochemistry.
…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Similar to the results of DNA transfection with the human AT constructs without the LeuGlyGly266-268GlyGlyAla substitution described above, the positive and negative controls presented anticipated positive and negative results. In addition, the amino acid substitution constructs at codon 69 exhibited substantially higher FORS1 antigen expression when combined with the LeuGlyGly266-268GlyGlyAla substitution, possibly due to the synergistic effects previously reported of the AT constructs containing the deletion of exon 3 or 4, or Met69Ser/Thr substitution in combination with the LeuGlyGly266-268GlyGlyAla substitution 16,24 . However, the Ter construct, H_ABO-A(Met69Ter & GlyGlyAla), did not present any FS activity even with the LeuGlyGly266-268GlyGlyAla substitution.
Figure 6FORS1 antigen expression after DNA transfection of a variety of human AT amino acid substitution constructs at codon 69 with the LeuGlyGly266-268GlyGlyAla substitution into COS1(B3GALNT1 + A4GALT) cells analyzed by immunocytochemistry.
…”
Section: Resultsmentioning
confidence: 76%
“…Because altered RNA splicing is frequent in cancer, this mechanism may explain, at least partially, the FORS1 appearance in some cancer cells/tissues of regular individuals in the Forssman antigen-negative human species 1723 . Additionally, we also serendipitously observed that the methionine to serine/threonine substitutions at codon 69 (Met69Ser/Thr) conferred weak FS activity 24 . Furthermore, co-introduction of one of those deletions or Met69Ser/Thr substitutions with the LeuGlyGly266-268GlyGlyAla substitution strengthened FS activity, possibly by the synergistic effects of altered intra-Golgi localization and/or protein conformation by the former and modified enzymatic specificity by the latter.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations